Plan de negocios para la creación de un restaurante de hamburguesas artesanales en la ciudad de Santa Marta (2023)
In order to meet the expectations of the fast-food consumer, a business model is structured that bets on the creation of a company that will produce and market artisan hamburgers in the city of Santa Marta, which will be prepared with a diversity of traditional ingredients. that will be very pleasing to the end customer. This is a product that belongs to the gastronomic sector, and it has been driven by the need to introduce a new concept to the traditional care schemes regarding the preparation of traditional fast food in the city of Santa Marta. The company intends to focus on the quality of the product and also on a functional, operational and commercial model, seeking in a transversal way the conquest of our customer segment. This research is of a mixed type, since it covers both types of qualitative and quantitative research to structure this business plan. For this, primary and secondary sources of information will be used, which will allow the effective development of the prospectus. At the institutional level, this research is developed following the guidelines of the Organizational Management area